Pengelolaan Arsip Elektronik Berbasis Teknologi - Machsun Rifauddin (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
Electronic archives have an important role in system of administration, it also as a valid instrument of evidence based on Undang-Undang No. 11 pasal 5 (1) 2008. Information technology progression requires the archive being processed electronically. The purpose of article to explain about what and how to manage archive electronic. This article was compiled based on the study of literature. The tools used to manage the electronic archives are hardware (computers, print scanner, and media storage) and software. Electronic archive different with print archive. Electronic archive has four cycles of creation and management of storage, distribution and use, maintenance, and disposition. Removal print archive into electronic archives can be done by way of scanning, conversion, Importing. Electronic archive storage can be done online, offline or nearline